2021
DOI: 10.1002/jmv.27122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study evaluating the efficacy of ivermectin in COVID‐19 treatment: A randomized controlled study

Abstract: Researchers around the world are working at record speed to find the best ways to treat and prevent coronavirus disease 2019 (COVID‐19). This study aimed to evaluate the efficacy of ivermectin for the treatment of hospitalized mild to moderate COVID‐19 infected patients. This was a randomized open‐label controlled study that included 164 patients with COVID‐19. Patients were randomized into two groups where Group 1 (Ivermectin group) included patients who received ivermectin 12 mg once daily for 3 days with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 32 publications
3
42
0
1
Order By: Relevance
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“… Ivermectin vs Standard care People: Adult patients with COVID-19 Setting: Inpatients (10 studies), Outpatients (7 studies) Intervention: Ivermectin Comparison: Standard Care (15 studies), HCQ (1 study), Lopinavir/ritonavir (1 study) Outcomes Absolute Effect Relative effect (95% CI) Number of studies Certainty of the evidence (GRADE) Without Ivermectin (Standard Care) With Ivermectin All-cause mortality Within 28 days of commencing treatment 53 per 1000 22 per 1000 RR 0.41 (0.19 to 0.92) 6 [ 17 , 45 , 47 , [117] , [118] , [119] ] (1079 patients) ⊕⊕⊖⊖ Low (serious risk of bias and serious imprecision Difference: 31 fewer per 1000 (95% CI: 43 fewer to 4 more) Mechanical ventilation Within 28 days of commencing treatment 40 per 1000 30 per 1000 RR 0.75 (0.23 to 2.43) 4 [ 88 , 117 , 118 ] (497 patients) ⊕⊕⊖⊖ Low (very serious imprecsion) Difference: 4 fewer per 1000 (95% CI: 31 fewer to 57 more) Serious adverse events End of treatment 7 per 1000 8 per 1000 RR 1.12 (0.21 to 5.88) 6 [ [42] , [43] , [44] , 47 , 120 , 121 ] (644 patients) ⊕⊕⊖⊖ Low (Very Serious imprecision, ) ...…”
Section: What Is the Effect Of Ivermectin In Reducing The Risk Of Disease Progression Or Mortality In Patients With Mild Covid-19 Comparementioning
confidence: 99%
“… 95% CI: 95% Confidence interval; RR: Risk ratio. References: [ 17 , 39 , 40 , [42] , [43] , [44] , [45] , [46] , [47] , [117] , [118] , [119] , [120] , [121] , [122] , [123] ]. Evidence adopted Australian guidelines for the clinical care of people with COVID-19, Available at: https://app.magicapp.org/#/guideline/5446/section/78706 .…”
Section: What Is the Effect Of Ivermectin In Reducing The Risk Of Disease Progression Or Mortality In Patients With Mild Covid-19 Comparementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple RCTs have studied ivermectin use in COVID-19 patients. Some RCTs could not found any clinical efficacy of ivermectin [63][64][65], while others have reported faster time to recovery of COVID-19 disease [66][67][68][69][70], a remarkable decrease of cytokines and inflammatory markers [67,68], faster viral clearance [71], or decrease in mortality rate [67,68] in participants who received ivermectin in comparison with the standard treatment protocol. Nevertheless, the majority of these RCTs had methodological issues like small sample sizes, various ivermectin dosages, and different concomitant drugs given to the patients.…”
Section: Synthetic Drugsmentioning
confidence: 99%